Evaluasi Program Penguatan Pendidikan Karakter di MAN 3 Sleman - Aji, Handaru Baskara; Rosa Kamelia; Habiburrahman; Kurniawan, Ilham (Journal of Practice Learning and Educational Development, 2025)
Character education is a systematic and continuous effort to shape the personality of citizens so that they possess inner strength, critical thinking, and strong character, and act based on values, norms, responsibilities, and social morality. A morally upright and ethical young generation with high competence and competitiveness is crucial for Indonesia as future leaders in preserving character amidst the negative influences of modern advancements. Periodic program evaluations are essential to maintaining the quality of a program. This study employs a qualitative descriptive approach, with the researcher serving as the primary instrument to understand phenomena occurring during the research activities. The CSE-UCLA evaluation model includes several stages, such as Need Assessment, Program Planning, Formative Evaluation, and Summative Evaluation. Additionally, the CSE-UCLA model aims to assess the effectiveness of the Strengthening Character Education program. The purpose of the evaluation is to measure the success or achievement level of a program, resulting in decisions about whether to follow up, continue, or terminate the program. This study focuses on evaluating the Strengthening Character Education program using the CSE-UCLA model. The evaluation results indicate that the improvement of the SCE program at MAN 3 Sleman has achieved its objectives and aligns with the planned goals